Simulation of OFDM over fiber for wireless communication system - Chahine, Ahmad Said (2007)
Radio-over-fiber (RoF) technology has several benefits such as larger bandwidth, reduced power consumption etc. that has made it an attractive implementation option for various communication systems. Orthogonal Frequency Division Multiplexing (OFDM) is seen as the modulation technique for future broadband wireless communications because it provides increased robustness against frequency selective fading and narrowband interference, and is efficient in dealing with multi-path delay spread. This project investigates the feasibility of Orthogonal OFDM as a modulation technique to transmit the basebans signal over fiber. Laser diode and photodiode have been modeled and used as optical modulator and optical demodulator respectively. Results from a MATLAB/SIMULINK system model, which show the QPSK-OFDM transmitted and received signal before and after the transmission over fiber, power spectrum before and after the transmission over fiber, constellation before and after channel estimation. The model of this project can be used with different wireless communication systems such as Wireless LANs and Digital Video Broadcasting (DVB) and it is supporting to the 4th generation cellular systems.